Unlocking Full Discharge Capacities of Poly(vinylphenothiazine) as Battery Cathode Material by Decreasing Polymer Mobility Through Cross‐Linking. Issue 33 (14th October 2018) - Otteny, Fabian; Kolek, Martin; Becking, Jens; Winter, Martin; Bieker, Peter; Esser, Birgit
Abstract: Organic cathode materials are a sustainable alternative to transition metal oxide‐based compounds in high voltage rechargeable batteries due to their low toxicity and availability from less‐limited resources. Important criteria in their design are a high specific capacity, cycling stability, and rate capability. Furthermore, the cathode should contain a high mass loading of active material and be compatible with different anode materials, allowing for its use in a variety of cell designs. Here, cross‐linked poly(3‐vinyl‐ N ‐methylphenothiazine) as cathode‐active material is presented, which shows a remarkable rate capability (up to 10C) and cycling stability at a high and stable potential of 3.55 V versus Li/Li + and a specific capacity of 112 mAh g −1 . Its use in full cells with a high mass loading of 70 wt% is demonstrated against lithium titanate as intercalation material as well as lithium metal, which both show excellent performance. Through comparison with poly(3‐vinyl‐ N ‐methylphenothiazine) the study shows that changing the structure of the redox‐active polymer through cross‐linking can lead to a change in charge/discharge mechanism and cycling behavior of the composite electrode. Poly(3‐vinyl‐ N ‐methylphenothiazine) in its cross‐ and non‐cross‐linked form both show excellent results as cathode‐active materials with variable specifications regarding specific capacity, cycling stability, and rate capability. Abstract : The full discharge capacity of poly(vinylphenothiazine) as battery cathode material is unlocked by cross‐linking. This leads to a reduction in polymer mobility and prevention of rearrangement processes. The cross‐linked polymer shows a high cycling stability and rate capability and excellent performance in full cells with a high mass loading of 70 wt% versus lithium and lithium titanate.